The influence of individual and organizational factor on external auditor whistleblowing practice in government-linked companies (GLC'S) / Aida Maria Ismail, Raja Muhamad Safuan Raja Mamat and Razinah Hassan. - Ismail, Aida Maria; Raja Mamat, Raja Muhamad Safuan; Hassan, Razinah (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2018)
Whistleblowing is a report on any corporate wrongdoing that occurs in organisations. There are many companies that bankrupt or suffer loss due to unethical behaviour such as mismanagement, misuse of company funds, money laundering, and manipulation of income statement for private advantage without considering the employees’ or shareholders interest. This study is conducted to examine the factors that could motivate whistleblowing practices by external auditors of Government Linked Company (GLCs). Several predictive variables have been considered, such as individual and organizational factors. However, the findings are still considered as inclusive, especially in Malaysia. 184 respondents from top three audit firms had completed the given questionnaire that was used for the analysis. This study showed that the sample auditors for this study were highly likely to become whistleblowers and individual moral reasoning and audit firms organizational structure have a significant relationship towards external auditor whistleblowing practices. Meanwhile, job satisfaction does not have significant relationship toward external auditor whistleblowing practice. The result of this study will be helpful to the GLCs and audit firms to increase their ethical awareness and at the same time, improve the confidence level of the stakeholders and public at large towards their company.